2018
DOI: 10.1186/s12944-017-0648-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of anthropometric indices to identify dyslipidemia among adults in Jilin Province: a cross-sectional study

Abstract: BackgroundDyslipidemia and other cardiovascular disease (CVD) risk factors have a strong association with obesity. Anthropometric indices have been widely used to evaluate obesity in clinical and epidemiological studies. We aim to investigate association between serum lipid levels and different anthropometric indices.MethodsOur study included 17,554 participants. We mainly investigated area under the receiver operating characteristic (AUROC) curves and optimal operating points (OOPs) between the anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…BMI is the most widely used measure to diagnose overweight and obesity, whereas WC and WHtR better indicator of intraabdominal fat, have been suggested to be more accurate to predict CM than BMI. 24,25,27,[38][39][40] Results of the current study demonstrated a significant correlation between most of the anthropometric indicators of adiposity and CM risk parameters. The strongest associations were observed with WHtR and WC.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…BMI is the most widely used measure to diagnose overweight and obesity, whereas WC and WHtR better indicator of intraabdominal fat, have been suggested to be more accurate to predict CM than BMI. 24,25,27,[38][39][40] Results of the current study demonstrated a significant correlation between most of the anthropometric indicators of adiposity and CM risk parameters. The strongest associations were observed with WHtR and WC.…”
Section: Discussionsupporting
confidence: 52%
“…Evidence from numerous studies demonstrated the association between adiposity and the risk of certain noncommunicable diseases. [24][25][26][27][28] Different body adiposity indicators were associated with CM risk. 12, [29][30][31][32][33][34][35][36][37] The major anthropometric indicators used to predict the CM risk include BMI, WHtR, and WC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BRI is limited in predicting percentage of fat mass in elite athletes when compared with other commonly and readily available field methods such as bio‐impedance analysis or skinfold prediction models 63 . Several recent studies have shown that BRI could be used as an adipose indicator for determining the presence of eccentric left ventricular hypertrophy, 64 hyperuricaemia, 41,65 arterial stiffness, 66–69 CVD, 70,71 diabetes, 41,72–75 dyslipidaemia, 41,76–78 hypertension 41,79,80 and MetS 41–55 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, the amount and distribution of VAT and SAT determine different body shapes [19]. We have previously shown that BRI is a good predictor for categories of abnormality based on either one/two serum lipid indices or three/more serum lipid indices in women and that ABSI has the weakest predictive power [20]. In the present study, we further investigated the capacity of the ABSI and BRI to identify people with diabetes, and determined whether ABSI and/or BRI was superior to the traditional overall adiposity index, BMI, in Northeast China.…”
Section: Introductionmentioning
confidence: 99%